(2b+1)-by=4

Simple and best practice solution for (2b+1)-by=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2b+1)-by=4 equation:


Simplifying
(2b + 1) + -1by = 4

Reorder the terms:
(1 + 2b) + -1by = 4

Remove parenthesis around (1 + 2b)
1 + 2b + -1by = 4

Solving
1 + 2b + -1by = 4

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + 2b + -1 + -1by = 4 + -1

Reorder the terms:
1 + -1 + 2b + -1by = 4 + -1

Combine like terms: 1 + -1 = 0
0 + 2b + -1by = 4 + -1
2b + -1by = 4 + -1

Combine like terms: 4 + -1 = 3
2b + -1by = 3

Reorder the terms:
-3 + 2b + -1by = 3 + -3

Combine like terms: 3 + -3 = 0
-3 + 2b + -1by = 0

The solution to this equation could not be determined.

See similar equations:

| 1/5x-4=1/2x-1/5x | | 7x=524.586 | | 0.05=2.29y+y | | 23-4x=12x+126 | | 15t=17+8-24 | | 4x+.80=25 | | 8k-5=51 | | 9w-26=28 | | 2x-4(x-5)=-6+5x-2 | | 5(10-4x)=290 | | 5(4)=16x | | 5t+4=36 | | 79=5u+14 | | -29(t+253)=406 | | -12/x=3-18/x-4 | | 5x+10=2+18 | | 3/6=13/x | | 79=u+14 | | 5x+10=2+15 | | 108=8y-3x | | -35=-5+5y | | n+(-9)=-9 | | 5x+10=2+20 | | (2+2y)+(3+5c)= | | 2(2x-3)-2x^2=(3-2x)x | | 1(x+15)=1x | | 5(x+3)=16y | | -11(k-862)=-803 | | 2u+11=51 | | 18p+36p=4884 | | 5x-1=19-4x | | 12x+8=18x-3 |

Equations solver categories